A Study of the Hadith on Sincerity in Sahih Bukhari and Its Implementation in Islamic Character Education - Muhammad Ridhoni Al Arif; Romlah Abu Bakar Askar; Munzir Suparta (Penerbit Hellow Pustaka, 2025)
Character education is the process of instilling certain values ​​and attitudes in students, while providing them with a foundation to develop their own unique characteristics as they interact in society. The emphasis on the concept of character education, in this context, refers to the teachings taught by the Prophet Muhammad in his hadiths. The hadiths of the Prophet Muhammad cover the ikhlas which is considered important to be studied and applied in daily life. This concept is an important focus in research, with the aim of understanding how character is formed, the types of character that exist, and how this character can be applied in daily life, especially from the perspective of the authentic hadith of Bukhari. This study aims to provide a better understanding to parents, educators, and students about the moral values ​​taught by the Prophet Muhammad through the hadith, with the hope that they will be able to implement these teachings in their daily life practices. The implementation of these values ​​is expected to create individuals who have good character, morals, and are full of compassion for others.